Analisis Pengaruh Motivasi Karir, Motivasi Ekonomi, Pengalaman Kerja Dan Biaya Pendidikan Pada Minat Mengikuti Pendidikan Profesi Akuntansi(PPAK) (Studi Empiris Pada Alumni S1 Jurusan Akuntansi) - Kurniawan, Dani, Dr. Triyono, SE, M.Si (2017)
The purpose of this research is to investigate the effect of career motivation, economic motivation, work experience and school fee in interest to following the accounting profession education. The technique in this research is convinince sampling, the sampel is amount to 100 from alumnus of accountant. The analysis is multiple linear analysis. The result of this study show that career motivation, economic motivation, work experience and school fee is significant influential in interest to following the accounting profession education.